Patient mental attitude: a systematic review - Eri H. Jubhari; Kezia Rachellea (Journal of Dentomaxillofacial Science, 2020)
Objective: To review the classifications of denture patientâ€™s mental attitude in order to expand readerâ€™s knowledge and help practitioners to confront their patient.Methods: Electronic search in internet to find articles which were published in last 20 years with keywords â€œpatient mental attitudeâ€ and â€œhouse classificationâ€. Articles were then selected by reviewing the title and abstract.Results: Based on data search, there are eight journal articles that suitable with the inclusion criteria.Conclusion: It is important for dentists to recognize patientâ€™s mental attitude before patientâ€™s general condition to help dentist to communicate and deal with patient along their mental attitude, in order to create a bond of trust between patient and practitioner, facilitate the treatment procedure and make a better treatment result.